IL-17 and Th17 cells in systemic sclerosis: a comprehensive review - Bălănescu Paul; Bălănescu Eugenia; Bălănescu Anca (Sciendo, 2017)
T cells (especially T helper cells) seem to be strongly associated with systemic sclerosis pathogenesis. Th17-IL-17 axis was proved to be involved in the pathogenesis of multiple autoimmune diseases. By performing a comprehensive research of the literature indexed in PubMed database, the current review summarizes current knowledge related to Th17 and IL-17 in systemic sclerosis. While there is promising data suggesting inhibition of Tregulatory and Th1 signals on one hand and promotion of Th17 and Th2 signals on the other, studies that include prospective and integrated analysis of Tregulatory, Th17, Th1, Th2 (cells and derived cytokines) on the same cohort of Ssc patients are warranted.